Early Systemic Scleroderma – A Modern Diagnostic Algorithm - Zohirovna, Mukhitdinova Gulshan; qizi, Shokirova Mexruza Komiljon (American Journal of Bioscience and Clinical Integrity, 2024)
Systemic connective tissue diseases encompass a group of chronic disorders affecting the connective tissues of the body, with systemic scleroderma (SSD) being one of the most severe forms. SSD is characterized by progressive fibrosis, which involves excessive collagen deposition in the skin and internal organs, leading to functional impairment and tissue damage. This disease also results in significant vascular abnormalities, including Raynaud's syndrome, as well as immune system dysregulation, manifesting in autoantibody production. The clinical course of SSD is often aggressive, with multiple organ involvement such as the lungs, heart, and kidneys. Patients may experience a range of complications, including pulmonary fibrosis, hypertension, and renal crisis. Given the disease's complexity, early diagnosis and a multidisciplinary treatment approach are essential to improve outcomes and manage symptoms. Current therapeutic strategies focus on symptom management, preventing further organ damage, and improving quality of life for those affected.